REPRESENTATIVES OF THE GENUS AMMOSIPHONIA HE, 1977 (FORAMINIFERA) FROM THE JURASSIC AND CARBONIFEROUS OF WESTERN SIBERIA - Marinov V.A. (My University, 2006)
The wide distribution of the genus Ammosiphonia in the Upper Jurassic and Carboniferous of Western Siberia is established for the first time. Six haplophragmoidid species of Western Siberia are assigned to this genus. The diagnosis of the genus is emended; the taxonomic positions and scopes of the species Ammosiphonia nonioninoides (Reuss), A. beresoviensis (Bulatova), and A. sibirica (Zaspelova) are revised; two new species, A. suprajurassica sp. nov. and A. valanginica sp. nov., are described. © Pleiades Publishing, Inc. 2006.
Keywords: AMMOSIPHONIA; CARBONIFEROUS; FORAMINIFERA; JURASSIC; WESTERN SIBERIA; Paleozoic::Carboniferous; Палеозой::Каменноугольная